Prevalence of caries in intellectually impaired children at Sekolah Semangat Maju, Taiping, Perak, Malaysia - Singh, Sanjit; Sasmita, Inne Suherna (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
Dental caries also known as tooth decay is a disease where a bacterial process damages the hard tooth structure. The aim of conducting this research was to obtain the prevalence of caries in the intellectually impaired children in Sekolah Semangat Maju, Taiping, Perak, Malaysia. The research was a descriptive research that utilized the survey technique. The population of the research was the students aged 7-17 years old from class 1 to class 5. The total sample for this research was 56 students. The students were examined for the presence of caries and the results were used to obtain the prevalence of caries in these subjects. The results from this study showed that the prevalence of caries based on the studentâs medical diagnose was 68.42% for autism students, 57.14% for cerebral palsy students, 91.67% for Downâs syndrome students, 100.00% for mental retardation students and 42.86% for slow learner students. The conclusion from this research was that the overall prevalence of caries in intellectually impaired children at Sekolah Semangat Maju Taiping, Perak, Malaysia is 67.89%.